ZAKAT DAN PAJAK: PERBANDINGAN MALAYSIA DAN INDONESIA - Royun Niswati Ahada; Tutik Hamidah (Fakultas Ekonomi dan Bisnis Islam, Universitas Islam Negeri Prof. K.H. Saifuddin Zuhri Purwokerto, 2021)
Zakat and tax are two things that are obligatory in the field of property, but they also have different philosophies, principles and characteristics. Zakat is part of the assets that must be issued by Muslims, while taxes are mandatory contributions by the people to the state and must be paid to the state in accordance with the rules that have been decided by the government. Here the researcher discusses the implementation of zakat and comparative taxes between Malaysia and Indonesia. This research uses literature study method with qualitative approach. Zakat and Taxes in Malaysia are managed by the central government through the territory of the respective states. Also, zakat is claimed to be a deduction from tax obligations, if the muzaki pays zakat at the Zakat Collection Center then, there is a reduction in zakat for tax reduction. Meanwhile in Indonesia, Zakat is managed by the Amil Zakat Agency and the Amil Zakat Institution formed by the Government. There is a regulation between zakat and taxes, in which there is a deduction of zakat and taxes if the zakat is deposited by muzaki through BAZNAS or LAZ by including proof of tax payment.